An investigation of the role of defect levels on the radiation response of synthetic diamond crystals when used as sensors for the detection of mammography X-rays. (September 2017) - Ade, Nicholas
Abstract: This study evaluates the role of defects on the performances of synthetic diamond sensors on exposure to mammography X-rays. Through systematic investigations, the main cause of instability of response of examined sensors necessitating pre-irradiation was isolated and ascribed to the presence of ambient light which has the effect of emptying shallow trapping levels. The changes in response between measurements in light and dark conditions varied from 2.8± 1.2% to 63.0± 0.3%. Sensitivities between 0.4 and 6.7 nC Gy −1 mm −3 determined for the sensors varied with defect levels. The study indicates that differences in crystal quality due to the presence and influence of defects would cause a discrepancy in the dosimetric performances of various diamond detectors. Once a sensor plate is selected (based on the influence of defect levels) and coupled to the probe housing with the response of the diamond sensor stabilised and appropriately shielded from ambient light, daily priming is not needed. Highlights: Presented are response characteristics of diamond detectors to mammography X-rays. Performances of the detectors were correlated to various isolated defect levels. Unstable response of detectors was attributed to the presence of ambient light. Sensitivity values of the diamond detectors were found to vary with defect levels.